The catalytic performance of Mn/TiWOx catalyst for selective catalytic reduction of NOx with NH3. (1st October 2016) - Chen, Qi-lin; Guo, Rui-tang; Wang, Qing-shan; Pan, Wei-guo; Wang, Wen-huan; Yang, Ning-zhi; Lu, Chen-zi; Wang, Shu-xian
Graphical abstract: Highlights: The NH3 -SCR activities of Mn/TiWO x catalysts are higher than that of Mn/TiO2 catalyst. The NH3 -SCR reaction over Mn/TiWO x (1:1) followed the Langmuir–Hinshelwood mechanism. The adsorbed NH3 species were more active than NO x species in the NH3 -SCR reaction. Abstract: A series of Mn/TiWO x catalysts were prepared and used in NH3 -SCR reaction for NO x emission control. The experimental results showed that the SCR activities of Mn/TiWO x catalysts are higher than that of Mn/TiO2 catalyst. After that, several characterization techniques including XRD, H2 -TPR, NH3 -TPD, XPS were used to investigate the effect of TiWO x support on the SCR performance of Mn/TiWO x (1:1) catalyst. The stronger reducibility and NH3 adsorption capacity, and more surface chemisorbed oxygen of Mn/TiWO x (1:1) should all contribute to its better SCR performance. Moreover, Mn/TiWO x (1:1) catalyst shows higher N2 selectivity, better SO2 tolerance and stability than Mn/TiO2 catalyst. The results of in situ DRIFT study revealed that the NH3 -SCR reactions over Mn/TiO2 and Mn/TiWO x (1:1) were all followed the Langmuir–Hinshelwood mechanism, in which the SCR reaction takes place between the adsorbed NH3 species and NO x species.